A longitudinal ICF-CY-based evaluation of functioning and disability of children born with very low birth weight. Issue 4 (December 2016) - Fontana, Camilla; Picciolini, Odoardo; Fumagalli, Monica; Mosca, Fabio; Bernardelli, Giuseppina; Leonardi, Matilde; Meucci, Paolo; Raggi, Alberto; Giovannetti, Ambra M.
Abstract : This paper aims to describe the longitudinal changes in disability, defined by the International Classification of Functioning, Disability, and Health – Children and Youth version (ICF-CY) biopsychosocial model, and developmental outcomes in a cohort of 56 very low birth weight children over 14–20 months. We used a neurofunctional assessment, the Griffiths Mental Development Scales-Revised: 2–8 years (Griffiths 2–8) to evaluate psychomotor development and the ICF-CY questionnaire for ages 0–3 and 3–6 to address children's disability. Extension indexes on the basis of ICF-CY categories were computed, and longitudinal change was tested. Complete follow-up was available for 55 children (mean age 36.7 months, SD 6.7). Considering the sample as a whole, neurofunctional assessment, Griffiths score and disability were basically stable. When the subsample of children with the higher baseline functioning was taken into account, some degree of worsening, in terms of an increase in the number of impairments and limitations, was found. Our results show that disability profiles, neurofunctional assessment and global development were basically stable, except for the subgroup of children who were in the intermediate/high-functioning cluster at baseline. The increased disability among these children might be because of the possibility to observe a wider set of age-specific problems, such as emotional, regulation and social abilities that are not detectable at an early stage of development and that might lead to reduced participation in social activities.